Impact Of Poetic Style For Pronunciation: A Systematic Literature Review - Wahyu Ariningsih, Tri (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Linguistics' field of pronunciation studies how words are pronounced and their intended meanings, arrangement, and classification of sounds as linguistic components. Then pronunciation is often associated in the pronunciation of a poem. It started with an oral tradition because previously poetry was made to be performed. Focusing on the phonemic inventory of poetry, several studies have found a non-arbitrary relationship between the frequency of occurrence of certain phoneme classes and the "emotional meaning", or emotional connotation of certain phonemes and their influence on the perception of the emotional tone of poetry. This research is classified as a collective enterprise and non-experimental descriptive research. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) was used in this study to collect data as part of the Systematic Literature Review (SLR). There were 113 data collected from various accredited and Scopus indexed sources such as Elsevier were mobilized to search the data. There are several papers that eliminated by problem topic, publication criteria, and the main outcome, namely the relationship between poetry and pronunciation in writing, 1 journal left. The main key keyword is also obtained, namely "additional language-learner". Then to determine the influence of poetic style on pronunciation, the author identified it through the use of rhyme and rhythm as well as physical engagement, this technology was able to capture "micro-moments" of peer-to-peer learning, illustrating how these techniques might be used to successfully engage students whose first language was not being used in the classroom.